2013
DOI: 10.1021/ja401769g
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Phosphorescence of Metal-Free Organic Materials in Amorphous Polymer Matrices

Abstract: Developing metal-free organic phosphorescent materials is promising but challenging because achieving emissive triplet relaxation that outcompetes the vibrational loss of triplets, a key process to achieving phosphorescence, is difficult without heavy metal atoms. While recent studies reveal that bright room temperature phosphorescence can be realized in purely organic crystalline materials through directed halogen bonding, these organic phosphors still have limitations to practical applications due to the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
403
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(409 citation statements)
references
References 30 publications
3
403
1
2
Order By: Relevance
“…Recently, Lee et al reported strong RTP induced in a solid transparent polymer (PMMA). 25,26 But the RTP was highly dependent upon the isotacticity of PMMA. In general, the preparation of highly isotactic polymers is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lee et al reported strong RTP induced in a solid transparent polymer (PMMA). 25,26 But the RTP was highly dependent upon the isotacticity of PMMA. In general, the preparation of highly isotactic polymers is rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The halogen bond [12] between different donors and PAHs/heterocyclic compounds possessing the planar large π-electron conjugation system as typical π-type acceptors can take on these tasks. Up to now, some excellent exploratory work has been reported [13,14].…”
Section: Halogen Bonding Acceptors As Phosphorsmentioning
confidence: 99%
“…In order to decrease thermal decay and quenching by oxygen, luminescent dyes are made as crystals, or are blended into polymers [11,[17][18][19]. For example, Kim et al [20] prepared a series of organic crystals that could emit bright phosphorescence at room temperature due to halogen bonding.…”
Section: Introductionmentioning
confidence: 99%